2019
DOI: 10.3390/cancers11091367
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging of Head and Neck Squamous Cell Carcinoma for Cancer Margin Detection in Surgical Specimens from 102 Patients Using Deep Learning

Abstract: Surgical resection of head and neck (H and N) squamous cell carcinoma (SCC) may yield inadequate surgical cancer margins in 10 to 20% of cases. This study investigates the performance of label-free, reflectance-based hyperspectral imaging (HSI) and autofluorescence imaging for SCC detection at the cancer margin in excised tissue specimens from 102 patients and uses fluorescent dyes for comparison. Fresh surgical specimens (n = 293) were collected during H and N SCC resections (n = 102). The tissue specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 40 publications
(82 reference statements)
0
93
0
1
Order By: Relevance
“…In particular, HSI has started to achieve promising results in the recent years with respect to cancer detection through the utilization of cutting-edge machine-learning algorithms [4,[19][20][21]. Several types of cancer have been investigated using HSI including both in vivo and ex vivo tissue samples, such as gastric and colon cancer [22][23][24][25], breast cancer [26,27], head and neck cancer [28][29][30][31][32][33], and brain cancer [34][35][36], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, HSI has started to achieve promising results in the recent years with respect to cancer detection through the utilization of cutting-edge machine-learning algorithms [4,[19][20][21]. Several types of cancer have been investigated using HSI including both in vivo and ex vivo tissue samples, such as gastric and colon cancer [22][23][24][25], breast cancer [26,27], head and neck cancer [28][29][30][31][32][33], and brain cancer [34][35][36], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In HSI digital histology, Ortega et al detected glioblastoma brain cancer in digital slides using a patch-based 2D-CNN approach [70]. Additionally, Halicek et al has employed very deep 2D-CNNs for classification, specifically the widely-used Inception v4 model (Figure 4) implemented in a sliding patch-based approach for head and neck squamous cancer [71] and thyroid and salivary gland cancers [72]. For comparing 2D-CNN and 3D-CNNs, in [73] Halicek et al explored spatial-spectral convolutions in 3D CNNs with 3D convolutional kernels to 2D approaches.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…In-vivo brain tumor detection ‡ [27] Deep learning 2D-CNN and 1D-DNN In-vivo brain tumor detection ‡ [69] 2D-CNN (Inception v4) Head and neck cancer [71] Salivary gland cancer [72] 2D-CNN and 3D-CNN Head and neck cancer [73] 2D-CNN (U-Net) Tongue cancer detection [74] Breast cancer [75] GAN HS image generation from RGB [76] RNNs, 2D-CNN and 3D-CNN Head and neck cancer detection [77] Publicly available datasets are marked with ‡ .…”
Section: Spatial and Spectral Features In Supervised Classificationmentioning
confidence: 99%
“…Otolaryngology-Head and Neck surgery is no exception. For example, studies have reported its use in diagnosing plethora of diseases of the head and neck through evaluation of patients' presenting complaint (for example, voice analysis) (7,8), or through evaluation of radiological, histological and/or endoscopic images (9)(10)(11). Other studies have reported its use in disease prognostication (for example, predicting hearing outcomes in sudden sensorineural hearing loss) (12), or in terms of predicting post-operative outcomes (for example, predicting post-operative complications in head and neck microvascular free tissue transfer) (13).…”
Section: Introductionmentioning
confidence: 99%